Counting and Commodifying - Kieran Healy (Washington University Journal of Law & Policy, 2011)
The Article discusses the issue of standardized testing and commodification in light of the U.S. education reform as related in the article “Testing as Commodification,” by Katharine Silbaugh. It says that Silbaugh offers information on the reform movement in education under the U.S. No Child Left Behind Act of 2001 (NCLB). It adds that Silbaugh is concerned on the corruption risk posed by NLCB's requirement that U.S. school make adequate yearly progress (AYP) based from standardized tests.
Keywords: Commodification; Educational change; School choice; School administration; School districts – Management; United States. No Child Left Behind Act of 2001; Standardized tests